An Interfacial Electron Transfer on Tetrahedral NiS2/NiSe2 Heterocages with Dual‐Phase Synergy for Efficiently Triggering the Oxygen Evolution Reaction. Issue 1 (6th December 2019) - Yang, Yang; Kang, Yikun; Zhao, Huihui; Dai, Xiaoping; Cui, Meilin; Luan, Xuebin; Zhang, Xin; Nie, Fei; Ren, Ziteng; Song, Weiyu
Abstract: Tetrahedral NiS2 /NiSe2 heterocages with rich‐phase boundaries are synthesized through a simultaneous sulfuration/selenylation process using Ni‐based acetate hydroxide prisms as precursor. Such a nanocage‐like NiS2 /NiSe2 heterostructure can expose more active sites, accelerate the mass transport of the ions/gas, and optimize the interfacial electronic structure, which shows a significantly lower overpotential of 290 mV at 20 mA cm −2 than those of NiS/NiS2 and NiSe2 as counterparts. The experimental characterizations and theoretical density functional theory (DFT) calculations unveil that the interfacial electron transfer from NiSe2 to NiS2 at the heterointerface can modulate the electronic structure of NiS2 /NiSe2, which further cooperates synergistically to change the Gibbs free energy of oxygen‐containing intermediates as the rate‐determining step (RDS) from 2.16 eV (NiSe2 ) and 2.10 eV (NiS2 ) to 1.86 eV (NiS2 /NiSe2 heterostructures) during the oxygen evolution reaction (OER) process. And as a result, tetrahedral NiS2 /NiSe2 heterocages with dual‐phase synergy efficiently trigger the OER process, and accelerate the OER kinetics. This work provides insights into the roles of the interfacial electron transfer in electrocatalysis, and can be an admirable strategy to modulate the electronic structure for developing highly active electrocatalysts. Abstract : Tetrahedral NiS2 /NiSe2 heterocages with rich‐phase boundaries are constructed by a simultaneous sulfuration/selenylation process. The interfacial electron transfer induces electronic structure modulation, thus cooperating synergistically to change rate‐determining step of oxygen‐containing intermediates in the oxygen evolution reaction (OER), which efficiently triggers the OER process, and accelerate the OER kinetics.